MECONIUM AND URINARY PATTERNS OF HEALTHY TERM NEWBORNS IN A TERTIARY CARE HOSPITAL OF WESTERN NEPAL- A PROSPECTIVE OBSERVATIONAL STUDY - Gupta, Badri Kumar; Kaphle, Raju; Gupta, Binod Kumar; Shresth, Sandeep; Kumar, Navneet Raj; Chaudhary, Nagendra (Journal of Universal College of Medical Sciences, 2018)
Introduction: The time of passage   of the newborn's   first meconium/stool    is an indicator of health and is used to screen for normal gastrointestinal   tract function. Most newborns urinate after birth, and this is an indication of normal renal function.  The aim of this study is to investigate   the meconium/stool and urinary patterns of healthy neonates so that it will help us to know the average time of passing meconium and Urine in newborns.Materials and Methods: A hospital based observational   study was conducted for a period of one year in healthy term newborns delivered at UCMS-TH, a tertiary care hospital in western Nepal.  Newborns with a gestational age of ≥ 37 weeks delivered by normal vaginal delivery or cesarean section were included. The newborns were fed either breast milk exclusively or a combination of breast milk and formula.  The frequency of meconium/stool and urine passage was recorded throughout their hospital stay with their timings.  Babies with congenital anomalies were excluded from the study (like imperforate anus, cleft lip and palate and spina bifida, colloidal baby).Results: Out of 1050 delivered babies,  5 were  excluded  from final analysis  as they did not meet the inclusion  criteria. The study showed  that  majority   (97.8%)  of newborns   passed  meconium   within 24 hours  of  life  while  only  2%  babies passed meconium  after  1st day (24 hours-48  hours)  suggesting  that majority  of newborns   pass stool within  48 hours of life. Also, the study showed  that majority (99.8%)  of babies  passed  urine within  first 12 hours while  only 0.2 % babies passed  urine between  13-24 hours suggesting  that most babies passed urine within first 12 hours. Conclusions: It was observed  in study that average  time of passage  of meconium  in most of the babies were before 48 hours and passage of urine  within  12 hours.Journal of Universal College of Medical ScienceVol. 6, No. 1, 2018, page: 8-10